Antibacterial Activity of Probiotics from Naniura Made with Nile Tilapia (Oreochromis niloticus) against Salmonella typhi - Cahyani, Agis Ayu; Agustini, Rudiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Microbial contamination in foodstuffs, particularly by pathogenic bacteria such as Salmonella typhi, is one of the leading causes of foodborne diseases, posing a serious threat to public health. The use of antibiotics to control infections has led to an increase in antibiotic resistance cases, thereby necessitating safer and more sustainable alternatives for controlling pathogenic bacteria. One potential approach is the utilization of natural probiotics derived from traditional fermented foods. Naniura, a traditional dish from North Sumatra made from raw freshwater fish without any heating process, is believed to contain lactic acid bacteria (LAB) that function as probiotics. This study aims to evaluate the antibacterial activity of probiotics derived from naniura made with Nile tilapia (Oreochromis niloticus) against Salmonella typhi. Nile tilapia was selected due to its high protein content and meat structure with fewer bones compared to common carp. The fermentation of naniura was carried out for 10 hours to optimize the growth of probiotic microorganisms. Probiotic isolation was followed by macroscopic, microscopic, and biochemical characterizations using TSIA, citrate, motility, indole, ornithine, MRVP, catalase, amylolytic, and proteolytic activity tests. The antibacterial activity was evaluated using the disk diffusion method against Salmonella typhi. The results showed that the isolated probiotics exhibited morphological and physiological characteristics indicative of the genus Enterococcus, and the diameter of the inhibition zone produced is categorised as strong, with an average inhibition zone of 12.8 mm ± 0.36 against Salmonella typhi. This study demonstrates that naniura made from Nile tilapia has the potential to serve as a natural source of effective antibacterial probiotics.